A.07 Efficacy, safety, and tolerability of ubrogepant for the acute treatment of migraine: a single-attack phase 3 study, ACHIEVE I. (5th June 2019) - Dodick, DW; Lipton, RB; Ailani, J; Lu, K; Lakkis, H; Finnegan, M; Trugman, JM; Szegedi, A; Davidovic, G
Abstract : Background: To evaluate efficacy, safety, and tolerability of ubrogepant, an oral CGRP receptor antagonist, for acute treatment of a single migraine attack.Methods: Multicenter, randomized, double-blind, placebo-controlled, parallel-group, single-attack, phase 3 study (NCT02828020). Patients randomized 1:1:1 to placebo, ubrogepant 50mg, or ubrogepant 100mg had 60 days to treat one migraine attack (moderate/severe pain intensity). Co-primary efficacy endpoints: pain freedom 2 hours post initial dose and absence of most bothersome migraine-associated symptom (MBS).Results: 1672 patients were randomized (safety population: n=1436; mITT population: n=1327). Mean age: 40.7 years; white (82.4%); female (87.5%). A significantly greater percentage of ubrogepant- than placebo-treated patients achieved pain freedom 2 hours post initial dose (50mg: 19.2%, adjusted P =0.0023; 100mg: 21.2%, adjusted P =0.0003; placebo: 11.8%). A significantly greater percentage of ubrogepant patients achieved absence of MBS (50mg: 38.6%, adjusted P =0.0023, 100mg: 37.7%, adjusted P =0.0023; placebo: 27.8%). The adverse event (AE) profile of ubrogepant was similar to placebo. The most common AEs (incidence ≥2% in any treatment group) within 48 hours of initial or optional second dose were nausea, somnolence, and dry mouth (all with incidence <5%).Conclusions: Both co-primary endpoints were met, with clinically meaningful effects on migraine headache pain and MBS. Ubrogepant was well tolerated, with no identified safety concerns.